Association Between Colchicine Treatment and Clinical Outcomes in Patients with Coronary Artery Disease: Systematic Review and Meta-analysis - Francesco Condello; Matteo Sturla; Bernhard Reimers; Gaetano Liccardo; Giulio G Stefanini; Gianluigi Condorelli; Giuseppe Ferrante (European Cardiology Review)
Background: The authors examined the association between colchicine treatment and clinical outcomes in patients with coronary artery disease. Methods: They performed a meta-analysis of randomised controlled trials (RCTs) involving patients with coronary artery disease receiving add-on colchicine to standard treatment compared with standard treatment. They used a mixed-effects Poisson regression model with random intervention effects to estimate the pooled incidence rate ratios (IRR) with 95% CI. Results: Ten RCTs were identified, including 12,819 participants followed up for a median of 6 months. Colchicine was associated with a lower risk of major adverse cardiovascular events (IRR 0.69; 95% CI [0.60–0.79]; number needed to treat for an additional beneficial outcome [NNTB] = 28); MI (IRR 0.77; 95% CI [0.64–0.93]; NNTB = 95) and ischaemic stroke (IRR 0.48; 95% CI [0.30–0.76]; NNTB = 155) and with a higher risk of gastrointestinal adverse events (IRR 1.69; 95% CI [1.12–2.54]; number needed to treat for an additional harmful outcome [NNTH] = 10). Colchicine did not affect all-cause death (IRR 1.09; 95% CI [0.85–1.40]), or cardiovascular death (IRR 0.75; 95% CI [0.51–1.12]), while it was associated with a higher risk of non-cardiovascular death (IRR 1.45; 95% CI [1.04–2.02]; NNTH = 396). Conclusion: The meta-analysis showed that the relative and absolute beneficial treatment effects of colchicine on cardiovascular outcomes outweigh the potential harm for non-cardiovascular mortality. Registration: PROSPERO 2021 CRD42021248874.